Kategoria teatralności w mediewistyce (projekt badań interdyscyplinarnych) - Dąbrówka, Andrzej (Litteraria Copernicana, 2008)
Theatrical means of interaction and social communication express meanings that should be analysed with a uniform apparatus. A category of execution of a communication act (performance) must take a central place in it. In rhetoric it is covered with the fifth canon (action or pronuntiatio). The report informs about three research projects including these problems.